Pengaruh Penyuluhan Kesehatan Tentang Pencegahan Kanker Serviks Melalui Audiovisual Terhadap Pengetahuan Wanita Usia Subur - Fiki Nurul Izmi; Sri Utami; Yulia Irvani Dewi (Jurnal Vokasi Keperawatan (JVK), 2023)
The provision of health education using audiovisual media can attract attention and convince women of childbearing age to increase their knowledge to prevent cervical cancer. This study aims to determine the influence of health counseling through audiovisual media on WUS knowledge at the Simpang Tiga Inpatient Health Center Pekanbaru. This study used a quasi-experimental design with a Non-Equivalent with Control Group design. The sampling technique used was purposive sampling of 34 respondents divided into 17 control group respondents and 17 experimental group respondents. The data analysis used is univariate and bivariate analysis using paired T test and Independent T test. The majority of respondents aged 41-49 years were 15 respondents (44.1%), Javanese tribesmen were 16 respondents (47.1%), high school education level 22 respondents (64.7%), occupational housewives respondents were 25 respondents (73.5%), most multipara as many as 22 respondents (64.7%). The results of statistical tests show that there is an influence of health counseling on cervical cancer prevention through audiovisual on WUS knowledge about cervical cancer prevention with a p value (0.000) < α (0.05). Health education using audiovisual media about cervical cancer prevention affects WUS knowledge, because the use of audiovisual media is more attractive so that it can be accepted by respondents with five senses. The results of this study can be one of the nursing interventions in increasing WUS knowledge related to cervical cancer prevention, especially through audiovisual.